Pengaruh Penambahan Steel Slag Dan Abu Terbang (Fly Ash) Terhadap Sebagian Sifat Beton Segar Dan Beton Keras - Randi Yuzti Ramadhan; Alex Kurniawandy; Zulfikar Djauhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This research study explained the effect of the addition of fly ash substitution of cement and steel slag substitution of sand against most properties of fresh concrete and hard concrete. This study aimed to determine the effect of fly ash and steel slag to most properties of fresh concrete and concrete hard to compare the results obtained with normal concrete so it can produce higher levels of tolerance in using a mixture of fly ash and steel slag on concrete. Testing and analysis done is workability, compressive strength, tensile strength, absorption, and porosity variations additions to the concrete normal quality 0% fly ash + 0% steel slag and 10% steel slag + 10% fly ash using portland composit cement with ordinary water immersion for 28 and 56 days. From the research results of mixing 10% steel slag + 10% fly ash in concrete obtained lower results on the testing of compressive strength and tensile strength apart than normal concrete, but the test results are still within the limits of the quality of the plan in order to obtain higher levels of tolerance is 10% , As for testing the absorption and porosity values generated in the concrete mix is higher than normal concrete.Keywords: steel slag, fly ash, workability, compressive strength, tensile strength, absorption, and porosity.